Effects of Retrogression and Re-aging Heat Treatments on Microstructure, Phase Transformations, Hardness, and Dry Sliding Wear in Powder Bed Laser Fusion/ AlSi10Mg - Koç, Ebubekir; Tütük, İbrahim; Cingöz, Umut Can; Özer, Gökhan (Springer, 2025)
In this study, retrogression and re-aging (RRA) heat treatment was applied to AlSi10Mg samples produced by the laser powder bed fusion (LPBF) technique at different temperatures and times. The microstructure and phase changes of RRA heat treatment were investigated using optical microscopy (OM), scanning electron microscopy (SEM), energy-dispersive x-ray (EDX) analysis, and x-ray diffraction (XRD) techniques. Hardness changes were determined using the Vickers microhardness (HV) method, and wear behavior was investigated through the dry sliding wear method. The results were compared with those of conventional T6 heat treatment. It was found that RRA heat treatment caused a more homogeneous Si distribution in the microstructure and improved hardness and wear resistance compared to traditional T6 heat treatment.
Keywords: AlSi10Mg; Phase Analysis; Laser Powder Bed Fusion (LPBF); Retrogression and Re-Aging (RRA); Wear Properties